On Making Sense of Research Commercialization and Entrepreneurship among Natural Scientists - Heinonen, Jarna; Paasio, Kaisu (Finland, 2025)
Universities are expected to solve societal challenges and bring value to the society through knowledge transfer and innovations, for example. This implies interaction with businesses and research commercialization as well as scientists taking steps towards entrepreneurship. Research on academic entrepreneurship and research commercialization acknowledge tensions between academia and business. At the same time, the ways in which individuals inhabiting these two different spheres interpret them remain scarcely studied. We explore the sensemaking processes of natural scientists narrating their work in which science and business are (supposed to be) combined in different ways, and ask how natural scientists make sense of research commercialization and entrepreneurship.
Drawing mainly from interview and learning reflection materials collected in the frame of a Nordic Centre of Excellence research programme, ‘NordAqua’, we focus on individuals in academia and the stories they tell about their work and collaboration with industry. Our study provides new insights on the complex-perceived relation between academia and business, and contributes by offering an enabling researcher-centred entrepreneurial narrative with new nuances and layers on entrepreneurship and related motives.